CHARACTERISTICS OF NON-STEROIDAL ANTI-INFLAMMATORY DRUG USE IN GERIATRIC OUTPATIENTS WITH MUSCULOSKELETAL DISEASES AT DONG NAI GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of non-steroidal anti-inflammatory drug (NSAID) use among geriatric outpatients with musculoskeletal diseases at Dong Nai General Hospital in 2025. Methods: Cross-sectional description, information collected from records, and electronic prescriptions on 460 geriatric patients being treated as outpatients for musculoskeletal diseases. Results: A total of 460 patients were included in the analysis, with a predominance of females (53%) and a mean age of 70.51 ± 8.55 years. Osteoarthritis was the most common diagnosis (51.1%). Aceclofenac (26.3%) and dexibuprofen (25.0%) were the most frequently prescribed NSAID. Most prescriptions were oral formulations (84.1%), with low and moderate doses accounting for the majority (95.4%). The rate of co-prescription of proton pump inhibitors (PPIs) for gastrointestinal prophylaxis was 84.1%. Among patients with comorbidities, NSAID were mainly prescribed at moderate doses, with limited use of high doses. The mean prescription duration was 10.45 ± 2.99 days, with 8–14 days being the most common duration (69.1%). Conclusion: NSAID use in geriatric patients was predominantly oral and at low to moderate doses, with aceclofenac and dexibuprofen being the most commonly prescribed. Most patients received PPI co-therapy for gastrointestinal protection, and the typical prescription duration ranged from 8 to 14 days.
Keywords: NSAIDs, outpatient, geriatrics.